Plant plasma membrane proteomics for improving cold tolerance - Takahashi, Daisuke; Li, Bin; Nakayama, Takato; Kawamura, Yukio; Uemura, Matsuo (Frontiers in Plant Science, 2013)
Plants are always exposed to various stresses. We have focused on freezing stress, which causes serious problems for agricultural management. When plants suffer freeze-induced damage, the plasma membrane is thought to be the primary site of injury because of its central role in regulation of various cellular processes. Cold tolerant species, however, adapt to such freezing conditions by modifying cellular components and functions (cold acclimation). One of the most important adaptation mechanisms to freezing is alteration of plasma membrane compositions and functions. Advanced proteomic technologies have succeeded in identification of many candidates that may play roles in adaptation of the plasma membrane to freezing stress. Proteomics results suggest that adaptations of plasma membrane functions to low temperature are associated with alterations of protein compositions during cold acclimation. Some of proteins identified by proteomic approaches have been verified their functional roles in freezing tolerance mechanisms further. Thus, accumulation of proteomic results in the plasma membrane is of importance for application to molecular breeding efforts to increase cold tolerance in crops.